Development and Evaluation of Chitosan and Aloe Vera Gel Mucilage Interpolymer Complex-Based Mucoadhesive Buccal Films of Tramadol Hydrochloride (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To develop and evaluate interpolymer complex based buccal mucoadhesive films of Tramadol Hydrochloride. The interpolymer complex was prepared by using Chitosan and Aloe vera gel mucilage. Materials and Methods: In present study the inter polymer complex is formed between mucoadhesive polymer chitosan and aloe vera gel mucilage. The resulted interpolymer complex is used to prepare buccal mucoadhesive films of Tramadol Hydrochloride, an opioid analgesic. Other excipients includes glycerin as plasticizer, a combination of Sodium Dihydrocholate and EDTA sodium salt as permeation enhancers and a backing layer of 1% ethyl cellulose is placed on each film to ensure unidirectional drug release to systemic circulation. The solvent casting method is used to prepare buccal films and evaluated for bioadhesion strength, tensile strength, swelling index, ex vivo diffusion and in vitro dissolution. Results and Discussion: Formulations are prepared and optimized by 32 factorial design. Formulation F7 was found to be optimized formulation which contained 50 mg drug, 100 mg IPC and 2% glycerin as plasticizer. Thus, this study suggests that interpolymer complex between chitosan and aloe vera gel mucilage can act as a potential mucoadhesive polymer system for buccal delivery of a drug like Tramadol Hydrocholride. Conclusion: In this study novel buccoadhesive film was developed using Inter polymer complex between chitosan and aloe vera gel mucilage. Film was releasing drug over a period of 8hr directly to systemic circulation through buccal mucosa. The extensive first pass metabolism of a drug was prevented to a great extent.